Motor entropy influence on sport results: Usain Bolt's record-breaking race example - Pomerantsev, A. A. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to estimate Usain Bolt's motor entropy and to calculate its effect on athletic performance. The paper analyzes momentary velocity for Usain Bolt in the men`s 100 m final at the 2009 IAAF World Championships. Applied to results in cyclic sports, motor entropy depends on the ability to reproduce the most effective running stride. Any variations negatively affect to sports performance and lead to increasing of entropy. We identified Shannon entropy for peaks (4.5 bit) and troughs (2.9 bit) of intracyclic velocity. Numerical simulation of momentary velocity with zero entropy shows that Usain Bolt`s time could be 9.42 s instead 9.58 s. Zero entropy means absolute body control without technique inaccuracies and full realization of the motor potential. Motor entropy is one of the factors that determine athletic performance.